Changing priorities, shifting narratives: Remapping rural livelihoods in Africa's artisanal and small-scale mining sector. (May 2022) - Hilson, Gavin; Hu, Yanfei
Abstract: This paper presents fresh ideas on why, in sub-Saharan Africa, people choose to engage in artisanal and small-scale mining (ASM) – low-tech, labour-intensive mineral extraction and processing – for lengthy periods. It nuances claims that ASM is largely 'poverty-driven' by weighing in more closely on the fates of individuals in the region who turn to the sector for income out of desperation. A closer inspection of the livelihood trajectories of these people reveals that many have managed to overcome challenging work conditions and position themselves to use ASM as a 'platform for wealth creation'. An analysis of these experiences reveals a more comprehensive picture of ASM's complexities, as well as illuminates further the sector's economic importance in sub-Saharan Africa. A case study of the gold-rich locality of Prestea, one of Ghana's most strategic ASM corridors and where numerous people who initially pursued work in the sector have managed to accumulate income and open their own businesses and/or invest in the community, is used to reinforce these points. A more complete picture of ASM livelihood trajectories would go a long way towards fortifying the case for formalizing and supporting the sector, and, more generally, making it more of a focal point of rural poverty alleviation and development strategy in sub-Saharan Africa. Highlights: In sub-Saharan Africa, artisanal and small-scale mining (ASM) is largely poverty-driven. Many people who were initially driven to ASM because of hardship have managed to accumulate savings. These people have used these savings creatively and reinvested elsewhere. 'A platform for wealth creation' is introduced here as a category for these particular livelihood trajectories. The case of Prestea, Ghana, illustrates how poverty-driven groups use ASM as 'a platform for wealth creation'.